2015
DOI: 10.1177/0885328215605952
|View full text |Cite
|
Sign up to set email alerts
|

The effect of controlled microrobotized blasting on implant surface texturing and early osseointegration

Abstract: Surface topography modifications have become a key strategy for hastening the host-to-implant response to implantable materials. The present study evaluated the effect of three different carefully controlled surface texture patterns achieved through microrobotized blasting (controlled to high, medium and low roughness) relative to a larger scale blasting procedure (control) in early osseointegration in a canine model. Four commercially pure grade 2 titanium alloy implants (one of each surface) were bilaterally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
1
0
1
Order By: Relevance
“…The stability and integration of implants with bone also depends upon the nature of the interface . Data regarding bone contact from this study confirmed previous observations implicating a positive correlation between increased surface micro‐roughness and bone attachment (Figures and ) . In contrast to the above mentioned studies where the implants had initial direct bone contact, the present study was not originally designed for this evaluation, but for soft tissue and capsule evaluation upon the upper plate surfaces (Figures and ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The stability and integration of implants with bone also depends upon the nature of the interface . Data regarding bone contact from this study confirmed previous observations implicating a positive correlation between increased surface micro‐roughness and bone attachment (Figures and ) . In contrast to the above mentioned studies where the implants had initial direct bone contact, the present study was not originally designed for this evaluation, but for soft tissue and capsule evaluation upon the upper plate surfaces (Figures and ).…”
Section: Discussionsupporting
confidence: 86%
“…26 Data regarding bone contact from this study confirmed previous observations implicating a positive correlation between increased surface micro-roughness and bone attachment (Figures 6 and 7). 28,43 In contrast to the above mentioned studies where the implants had initial direct bone contact, the present study was not originally designed for this evaluation, but for soft tissue and capsule evaluation upon the upper (Figures 3 and 4). Therefore the implants, not being contoured to the bone, had limited initial direct bone contact along their surface apart from at the screw surfaces ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…As alterações micro ou nanométricas sobre as superfícies dos implantes, têm sido amplamente estudadas, pois atuam acelerando o processo inicial de cicatrização óssea, levando a uma estabilidade biomecânica mais precoce. Essas alterações são importantes tanto para a diferenciação e adesão dos osteoblastos durante a fase inicial de osseointegração, quanto para a fase de remodelação óssea em um segundo momento (Gil et al, 2016;Smeets et al, 2016).…”
Section: Introductionunclassified